The evolution of young people’s mental health during COVID-19 and the role of food insecurity: Evidence from a four low-and-middle-income-country cohort study - Porter, C; Hittmeyer, A; Favara, M; Scott, D; Sánchez, A (Royal Society for Public Health, 2022)
Objectives Provide evidence on how young people’s mental health has evolved in Low-and-Middle-Income-Countries (LMICs) during the progression of the COVID-19 pandemic. Identify particularly vulnerable groups who report high and/or continuously high rates of mental health issues. Study design Longitudinal, observational. Methods Two consecutive phone-surveys (August–October and November–December 2020) in Ethiopia, India, Peru and Vietnam interviewed around 9000 participants of a 20-year cohort study who grew up in poverty, now aged 19 and 26. Rates of at least mild anxiety/depression measured by GAD-7/PHQ-8 were each compared across countries; between males/females, and food secure/food insecure households. Results Overall, rates of at least mild anxiety and mild depression significantly decreased between mid and end-2020 in all countries but Ethiopia as COVID-19 infection rates fell. Females report higher rates of anxiety and depression in all countries but Ethiopia, however the gender gap is closing. Young people in food insecure households have not shown consistent improvements in their rates of anxiety and depression. Food insecure households are poorer, and have significantly more children (p < 0.05) except in Ethiopia. Conclusion Food insecurity is negatively associated with young people’s mental health and urgent support targeted towards the most vulnerable should be a priority. Further research into increasing rates of mental health issues in Ethiopia is needed.